Physician-prescribed museum visit benefits on mental health: results of an experimental study - Beauchet, Olivier; Moret, Adeline; Deveault, Melanie; Thiboutot, Claire; Parent, Nicole; Boyer, Hélène; Galéry, Kevin (Frontiers in Medicine, 2025)
BackgroundArt and cultural activities have been associated with health benefits. The effects of a physician-prescribed museum visit on the mental health of patients remain to unclear. This study aims to examine the effects of a single visit at the Montreal Museum of Fine Arts (MMFA, Montreal, Quebec, Canada), prescribed by a physician, on the wellbeing and quality of life of patients living in Montreal (Quebec, Canada).MethodsThe study used a pre-post intervention, non-randomized single-arm, experimental design with prospective data collection. A total of 86 patients (mean age 51.5 ± 17.6, 82.6% female) completed the study. The intervention consisted in a single MMFA visit prescribed by a primary or secondary care physician. Well-being and quality of life were assessed before and after the MMFA visit using validated self-questionnaires completed on a web-based platform including the Warwick-Edinburgh Mental Well-being Scale (WEMWBS) and the EuroQol-5D (EQ-5D), respectively. Participants’ baseline characteristics were also recorded.ResultsThere was a significant improvement of both WEMWBS (≤0.001) and EQ-5D (p ≤ 0.002) scores between after and before the MMFA visit. The increase in WEMWBS score was positively associated with self-reported unhappiness (coefficient of regression beta (ß) = 15.15 with 95% confident interval (CI) = [4.30,25.99] and p = 0.007) and the presence an acute disease (ß = 10.76 with 95% CI = [3.15,18.37] and p = 0.006).InterpretationA physician-prescribed visit to the MMFA was associated with improved mental health. These results suggest that museums could play a valuable role as partners in care pathways for patients in primary and secondary healthcare settings.Clinical trial registrationhttps://clinicaltrials.gov/study/NCT05445453, identifier NCT05445453.